Determination of tensile properties of hemp-fiber bundle by using tensile testing equipment with raspberry Pi - Paiboon Limpitipanich (2018)
Tensile strength of some natural fibers such as hemp is higher than that of steel. To determine tensile properties of hemp fiber, a fiber or bundle is tensile tested with universal testing machine that is controlled by personal computer. This paper presents a small tensile testing equipment that is controlled by Raspberry Pi (RPi), a credit-card-sized single-board computer. General Purpose Input Output (GPIO) pins on RPi were used for controlling the machine crosshead and receiving the tensile load that apply to a hemp bundle. A stepper motor was used to drive the crosshead. Tensile load was measured by using a load measurement system included load-cell, instrument amplifier, and analog-to-digital converter. The applied load and extension were real-time displayed and continuously recorded throughout the test. Testing hemp-fiber bundles with the proposed equipment found that their tensile strength and Young's modulus were 446.75±184.36 MPa and 18.23±8.26 GPa, respectively. These results were in good agreement with the properties founded in other publications. Test results also found that hemp-fiber bundle with smaller diameter showed higher tensile strength than that of larger one. © (2014) Trans Tech Publications, Switzerland.